Porous single-crystal multi-element alloy catalyst, preparation thereof and application of porous single-crystal multi-element alloy catalyst in HER catalysis

Through the preparation method of porous single-crystal multi-alloy catalyst, the problem of unsatisfactory activity and stability of high-entropy alloys under acidic conditions is solved, and the efficient performance and cost reduction of acidic HER catalytic materials are achieved.

CN119800420AActive Publication Date: 2025-04-11CENT SOUTH UNIV

Patent Information

Application Number
CN202510297576.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-03-13
Publication Date
2025-04-11
Estimated Expiration
2045-03-13

AI Technical Summary

Technical Problem

The existing high-entropy alloy HER catalytic materials are mainly suitable for alkaline conditions, and it is difficult to obtain good hydrogen evolution activity and stability under acidic systems.

Method used

The preparation method of porous single crystal multi-alloy catalyst is adopted to construct catalytic materials suitable for acidic HER applications through constant current electrodeposition, transformation treatment and alkaline liquid modification.

Benefits of technology

Excellent hydrogen evolution activity and long cycle stability under acidic conditions are achieved, reducing the cost of the catalyst.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119800420A_ABST
    Figure CN119800420A_ABST
Patent Text Reader

Abstract

The invention belongs to the field of water electrolysis materials, and particularly relates to a porous single-crystal multi-element alloy catalyst and preparation and application thereof in HER catalysis, and the preparation method comprises the following steps: obtaining an electrolyte in which metal ions of M1, M2 and M3 are dissolved, placing a carrier in the electrolyte for constant-current electro-deposition treatment, and depositing on the carrier to form an M1-M2-M3 multi-element alloy; wherein M1 comprises at least one of zinc, gallium, indium and tin; m2 comprises at least one of iron, cobalt, nickel, copper, zinc, manganese and chromium; m3 comprises at least one of platinum, gold, silver, palladium and iridium; the total number of types of metal elements of M1, M2 and M3 is three or more; and carrying out transformation treatment on the carrier deposited with the M1-M2-M3 multi-component alloy at the temperature of 450-850 DEG C, and then carrying out modification treatment in alkali liquor, thereby obtaining the catalyst. The material provided by the invention can still show excellent long-cycle stability under acidic and large current conditions.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of catalysts for producing hydrogen by electrolysis of water, and in particular to an acidic HER catalytic material. Background Art

[0002] Hydrogen is a versatile energy carrier that can be produced by a variety of methods. Among them, hydrogen production by water electrolysis driven by renewable electricity generated by renewable energy such as wind power and solar energy is an effective and clean method, and is the most promising technology for achieving large-scale application of hydrogen energy and transferring it to industrial production.

[0003] Proton exchange membrane water electrolysis (PEMWE) is an advanced water electrolysis technology. It uses ultra-thin proton exchange membranes to transfer protons and isolate positive and negative electrodes, ensuring the safety of the electrolyzer. It also has advantages such as high current density and high conversion efficiency, and has attracted widespread attention. However, the highly corrosive acidic environment of PEMWE makes only a few precious metal-based electrocatalysts have excellent activity and stability. The representative catalyst in the hydrogen evolution reaction (HER) at the cathode is Pt / C, but the scarcity of precious metals leads to high catalyst costs, which to a certain extent limits the development of PEMWE. Therefore, some researchers have proposed to form a high-activity catalyst with low precious metal loading by alloying with other transition metals. When different metals or non-metals form alloys, due to the difference in chemical properties, electrons are induced to redistribute around the metal. Incorporating a small amount of transition metals can improve catalytic activity while reducing application costs, which is a feasible solution.

[0004] Multi-element alloys (alloys of three or more metal elements, among which alloys formed by 3-4 metals are usually identified as medium-entropy alloys; alloys formed by five or more metals are usually identified as high-entropy alloys) have gradually entered people's field of vision as a new type of material. Multi-element alloys have certain advantages in the field of electrocatalysis. The main reason is that the synergistic effect between the elements makes the hydrogen adsorption and desorption ability on the catalyst surface close to equilibrium, the hydrogen adsorption free energy is close to 0, and the performance of the catalyst is further improved.

[0005] The prior art also discloses some high entropy alloy HER catalytic technologies. For example, the Chinese patent document with publication number CN118166391A discloses a FeCoNiWCuOOH@Cu electrocatalyst and its preparation method and application. For another example, the Chinese patent document with publication number CN116288477A discloses a bifunctional high entropy nano alloy electrocatalyst and its preparation method. The high entropy electrode materials prepared by these technologies are usually used under alkaline conditions.

[0006] In summary, existing multi-element alloys such as high-entropy alloy HER materials are mainly suitable for alkaline hydrogen evolution applications, and are difficult to adapt to acidic HER application requirements, and it is difficult to obtain good hydrogen evolution activity and stability in acidic systems. Summary of the invention

[0007] In view of the problems existing in the existing electrocatalytic electrodes, the first object of the present invention is to provide a method for preparing a porous single crystal multi-element alloy catalyst, aiming to prepare a HER catalytic material that is adapted to the requirements of acidic HER applications and has both excellent hydrogen evolution activity and acidic stability.

[0008] The second object of the present invention is to provide a porous single crystal multi-element alloy catalyst prepared by the preparation method and its application in HER catalysis.

[0009] The third object of the present invention is to provide a water electrolysis device comprising the porous single crystal multi-element alloy catalyst of the present invention.

[0010] Acidic HER and alkaline HER have different systems and face different problems. For example, for acidic HER, it is necessary to focus on solving the problems of poor activity and stability caused by the migration of alloy elements under acidic conditions, especially under high current acidic conditions. In response to these industry problems, the present invention is the first attempt in the industry to propose an improved idea for constructing porous and single-crystal multi-element alloys, but early research and development showed that the successful implementation of this idea requires solving the problems of difficulty in synchronous construction and regulation of porous and single crystals, low mixing entropy caused by easy segregation and clustering of multi-element metals, and unsatisfactory homogenization. In response to this problem, the present invention has provided the following solutions after in-depth research:

[0011] A method for preparing a porous single crystal multi-element alloy catalyst comprises obtaining an electrolyte in which metal ions of M1, M2 and M3 are dissolved, placing a carrier in the electrolyte for constant current electrodeposition treatment, and depositing an M1-M2-M3 multi-element alloy on the carrier; wherein M1 comprises at least one element of Zn, Ga, In and Sn; M2 comprises at least one non-precious metal element of Fe, Co, Ni, Cu, Zn, Mn and Cr; M3 comprises at least one precious metal element of Pt, Au, Ag, Pd and Ir; the total number of types of metal elements of M1, M2 and M3 is more than 3; and the current in the constant current electrodeposition stage is 5-300 mA / cm 2 , the constant current electrodeposition time is 2min~2h;

[0012] The carrier deposited with the M1-M2-M3 multi-element alloy is subjected to transformation treatment at a temperature of 450-850°C, and then subjected to modification treatment in an alkaline solution to obtain the porous single crystal multi-element alloy catalyst.

[0013] The present invention shows that the innovative combination of the metals of the types M1 to M3, further combined with the constant current electrodeposition method, the current and time, and the subsequent transformation process and temperature and the subsequent alkali solution-assisted modification can achieve synergy, solve the problems of low mixing entropy of metals, easy formation of nanoclusters, easy segregation of metals, etc., and in situ construction of single crystals and new catalytic materials that are porous. Studies have shown that the catalytic materials with the characteristics obtained by the preparation method can unexpectedly adapt to the requirements of acidic HER applications, not only showing excellent catalytic activity, but also taking into account excellent acid resistance and stability, and can still show excellent long-cycle stability under acidic and high current conditions.

[0014] In the present invention, the combination of the metal M1-M3 elements, constant current electrodeposition, transformation and alkali solution modification is the key to solving the alloy nanoclustering and metal segregation, constructing porous and single crystal morphology, and improving its HER performance in an acidic system. Studies have also shown that the innovative use of metal M1 can be combined with the process to help optimize the mixing entropy of the metal, reduce metal nanoclustering, reduce the segregation of metal elements, optimize single crystal and porous structures, and help improve the interface bonding effect between the high entropy alloy and the carrier.

[0015] In the present invention, the total number of metal elements of M1, M2 and M3 is 3 to 6. For example, when the total number of types is 3 to 4, the obtained multi-element alloy catalyst can be understood as a medium entropy alloy, and when the number of types is 5 to 6, a high entropy alloy can be obtained.

[0016] In the present invention, the total number of types of metal elements of M1, M2 and M3 is 5 to 6.

[0017] In the present invention, the use of the M1, in combination with the constant current electrodeposition, transformation and alkali solution modification, can achieve synergy, facilitate the construction of the porous-single crystal multi-element alloy, and facilitate the improvement of the entropy value and homogenization effect, which helps to improve the activity and stability of the prepared material under acidic HER. Preferably, the M1 contains zinc.

[0018] The M2 comprises one or more of Fe, Co, Ni, Cu, Zn, Mn, and Cr, for example, Fe. Further, the M2 comprises 4 to 5 of the above elements. When M2 is multiple, the content of each element is ±10% of the average molar percentage in M2; for example, the molar amount of each element in M2 is the same.

[0019] The metal M3 includes Pt.

[0020] In the present invention, the molar ratio of M1, M2 and M3 is 500:1-10:1-10; further 500:4-5:1-5.

[0021] In the present invention, the water-soluble salt of the metals M1 to M3 can be dissolved in water to obtain the electrolyte. The water-soluble salt is, for example, at least one of the sulfates, nitrates, organic acid salts, chlorides, etc. of each metal.

[0022] In the present invention, the carrier may be any carrier known in the industry, for example, a carbonaceous carrier, and further may be at least one of carbon felt, carbon cloth, carbon paper, and titanium foam.

[0023] The weight ratio of the carrier to the M1-M2-M3 multi-element alloy is 1:0.001-0.1; further, it can be 1:0.003-0.02, and further, it can be 1:0.003-0.005.

[0024] In the present invention, the innovative use of metals M1 to M3 and the constant current electrodeposition process are combined, and the joint control of current and time is further coordinated, which is helpful for combination with other processes, and is beneficial to improving the entropy value of the material, improving the homogenized distribution of elements, and constructing adaptive porous and single crystal structures, which is beneficial to improving the long cycle performance of the material under acidic HER and high current.

[0025] In the present invention, the current of the constant current electrodeposition is 40-100 mA / cm 2 ; More preferably, 45 to 55 mA / cm 2 The constant current electrodeposition time is 15min~1h, preferably 20~25min. Studies have shown that under optimal conditions, the process can be further combined and coordinated to further improve the physical and chemical structure of the prepared material, improve its HER under acidic conditions and cycle stability under high current.

[0026] In the present invention, thanks to the combination of the metals M1 to M3 and constant current electrodeposition, further cooperation with the subsequent transformation treatment is conducive to improving the mixing entropy of the alloy, improving the homogenized distribution of the metal, and helping to synergistically construct a single crystal porous material. The study also shows that further optimization of the transformation process is expected to further synergistically improve the HER activity of the material under acidic conditions and the stability under high current.

[0027] Preferably, the transition temperature is 450-600°C, further 480-520°C. The holding time at the transition temperature is 0.5-10h; preferably 1-1.3h. Studies have shown that under optimal conditions, the process can be further combined and coordinated to further improve the physical and chemical structure of the prepared material, improve its HER under acidic conditions and cycle stability under high current.

[0028] The study also shows that the optimal transition temperature and time are expected to further synergistically improve the material's HER activity under acidic conditions and stability under high current.

[0029] The atmosphere in the transition stage is a reducing atmosphere, for example, a hydrogen-containing atmosphere, wherein the hydrogen content may be 2-20% by volume, or further may be 10-15% by volume.

[0030] In the present invention, on the basis of the constant current electrodeposition and transformation involving the metals M1 to M3, further modification treatment assisted by alkaline solution is further used to help give the material rich sites and synergistically construct the porous-single crystal multi-element catalytic material, which helps to improve the HER activity of the material under acidic conditions and the stability under high current.

[0031] In the present invention, the alkali solution is an aqueous solution of an alkaline solute, and the alkaline solute includes at least one of an alkali metal hydroxide and a carbonate; for example, it can be at least one of sodium hydroxide and potassium hydroxide. Potassium hydroxide is further preferred. Studies have shown that under preferred conditions, it can be further combined with the process to help further improve the physicochemical structure of the prepared material, improve its HER under acidic conditions and the cycle stability under high current.

[0032] In the alkali solution, the concentration of the alkaline solute is 0.1-5 M, further 1-4.5 M, and further 3-4.5 M. Studies have shown that under preferred conditions, the process can be further combined and coordinated to further improve the physical and chemical structure of the prepared material, improve its HER under acidic conditions and cycle stability under high current.

[0033] In the alkali solution modification process of the present invention, the transformed material is completely immersed in the alkali solution.

[0034] The time for the product after transformation treatment to be modified in alkali solution (alkali solution modification time) is 2~24h, and can be further 10~15h. Studies have shown that under optimal conditions, it can be further combined with the process to help further improve the physical and chemical structure of the prepared material, improve its HER under acidic conditions and cycle stability under high current.

[0035] The invention also provides a porous single crystal multi-element alloy catalyst prepared by the preparation method.

[0036] The research of the present invention shows that the special preparation method can synergistically construct the special physicochemical characteristics of the product, and the material with the characteristics prepared by the preparation method can unexpectedly improve the HER activity of the material under acidic conditions and the stability under high current.

[0037] The present invention also provides an application of a porous single crystal multi-element alloy catalyst prepared by the preparation method, which is used as a HER catalytic active component for catalyzing a hydrogen evolution reaction in an acidic solution.

[0038] The present invention also provides a water electrolysis device, which comprises the porous single crystal multi-element alloy catalyst prepared by the preparation method of the present invention, or is prepared by the porous single crystal multi-element alloy catalyst.

[0039] The device described in the present invention, in addition to comprising the new material described in the present invention, other components and structural relationships may be well-known, or may be reasonably controlled based on known means.

[0040] In the present invention, the device is any device that can achieve efficacy based on the HER reaction, such as a battery, a water electrolysis device, etc.

[0041] Beneficial Effects

[0042] The present invention innovatively combines the M1~M3 type metals in multiple combinations, further cooperates with the constant current electrodeposition method, the combination of current and time, and then cooperates with the subsequent transformation process and temperature and the subsequent alkali solution assisted modification, so that synergy can be achieved, and the problems of low mixing entropy of metals and metal segregation can be solved. In addition, a new catalytic material that is single crystal and porous can be constructed in situ. Studies have shown that the catalytic material with the characteristics prepared by the preparation method has excellent acidic HER catalytic activity and long cycle stability under high current.

[0043] The material of the present invention has a lower cost. For example, the precious metal content can be reduced to 16.1 μg / cm 2 , which greatly reduces the cost of the catalytic electrode.

[0044] The preparation method of the present invention is simple and efficient, and the processes of electrodeposition, transformation and modification can all be realized in industrial production, wherein the electrodeposition can adopt the industrially mature roll-to-roll electrodeposition process to realize continuous production, which is conducive to the large-scale preparation of this type of catalyst. BRIEF DESCRIPTION OF THE DRAWINGS

[0045] Figure 1 This is a transmission electron microscope (TEM) image of the porous single crystal high entropy alloy catalyst prepared in Example 1.

[0046] Figure 2 This is the element distribution diagram of the porous single crystal high entropy alloy catalyst prepared in Example 1.

[0047] Figure 3 This is a high-resolution transmission electron microscope (HRTEM) image and Fourier spectrum of the porous single crystal high entropy alloy catalyst prepared in Example 1.

[0048] Figure 4 The linear sweep voltammetry (LSV) curves of the porous single crystal high entropy alloy catalyst prepared in Example 1 and the commercial Pt / C catalyst after activation are shown.

[0049] Figure 5 The porous single crystal high entropy alloy catalyst prepared in Example 1 is 2 IT curve under current. DETAILED DESCRIPTION

[0050] The present invention will be further described and illustrated below in conjunction with specific embodiments and accompanying drawings:

[0051] A typical method for preparing a porous single crystal multi-element alloy catalyst according to the present invention comprises the following steps:

[0052] Step (1): A self-supporting carrier of a certain size is used as a working electrode and a platinum sheet is used as a counter electrode and placed in an electrolyte containing metals M1, M2 and M3. The current and time are adjusted to obtain a polycrystalline multi-element alloy supported on a carrier such as carbon felt, carbon cloth, carbon paper, or titanium foam by constant current electrodeposition.

[0053] Step (2): Take out the sample obtained in step (1) and place it in a vacuum oven to dry.

[0054] Step (3): placing the electrode material loaded with multi-element alloy obtained in step (2) in a tube furnace for transformation, adjusting the transformation time and temperature, and obtaining a transformed material.

[0055] Step (4): placing the transformation material obtained in step (3) in an alkaline solution for modification, wherein the alkaline solution used is a KOH solution or a NaOH solution, to obtain a porous single crystal multi-element alloy supported on a substrate.

[0056] M1 includes at least one element of Zn, Ga, In, and Sn; M2 includes at least one non-precious metal element of Fe, Co, Ni, Cu, Zn, Mn, and Cr; M3 includes at least one precious metal element of Pt, Au, Ag, Pd, and Ir; the total number of metal elements in M1, M2, and M3 is more than 3. As an optional solution, the metal in the electrolyte includes Zn, Fe, Co, Ni, Cu, and Pt.

[0057] The optional electrolyte includes zinc salts such as ZnSO4, other non-precious metal salts such as FeCl3, CoCl2, NiCl2, CuCl2 and precious metal salts such as H2PtCl6. As an optional solution, in the electrolyte, the concentration of ZnSO4 is 0.1~1mol / L; the concentrations of FeCl3, CoCl2, NiCl2 and CuCl2 are 0.5~200 mmol / L, further 0.5~10 mmol / L; the concentration of H2PtCl6 is 0.1~40mmol / L, further 0.1~2.5 mmol / L.

[0058] Preferably, the constant current electrodeposition time is 2 min to 2 h, further 15 min to 1 h.

[0059] Preferably, the current is 5-300 mA / cm 2 , further 40~100 mA / cm 2 .

[0060] In the present invention, a reducing gas H2 / Ar atmosphere is introduced into the tubular atmosphere furnace during the transformation process.

[0061] Preferably, the ratio of hydrogen to argon in the H2 / Ar atmosphere is 2:98 to 20:80.

[0062] Preferably, the transition temperature of the tubular atmosphere furnace is 450-850°C, further 450-600°C.

[0063] Preferably, the transformation time is 0.5 to 10 hours, further 0.5 to 2 hours.

[0064] In the present invention, the alkaline solution used in the modification process is a 0.1-4M KOH solution or a NaOH solution;

[0065] Preferably, the modification time is 2 to 24 hours, further 10 to 15 hours.

[0066] The invention also provides a porous single crystal multi-element alloy catalyst prepared by the preparation method.

[0067] Example 1

[0068] A method for preparing a porous single crystal high entropy alloy catalyst comprises the following steps:

[0069] Step (1): Place 1×1.3cm 2 Carbon felt is used as the working electrode (where the area immersed in the electrolyte can be 1×1 cm 2 ), a platinum sheet is placed as a counter electrode in an electrolyte (electrodeposition solution) for constant current electrodeposition to form a polycrystalline high entropy alloy on the carbon felt.

[0070] The electrodeposition solution includes M1 metal salt (ZnSO4 in this case), M2 metal salt (FeCl3, CoCl2, NiCl2 and CuCl2 in a molar ratio of 1:1:1:1), and M3 metal salt (H2PtCl6); wherein the concentration of the total metal element (the sum of metals M1, M2 and M3) in the electrodeposition solution is 0.1042 mol / L;

[0071] The molar ratio of metal M1:metal M2 and metal M3 is 500:5:1.

[0072] The weight ratio of carbon felt to total metal elements is 1:0.003;

[0073] The current of constant current electrodeposition is 50mA / cm 2 , the constant current electrodeposition time is 20min.

[0074] Step (2): Take out the sample obtained in step (1) and place it in a vacuum oven at 60°C to dry.

[0075] Step (3): The carbon felt loaded with high entropy alloy obtained in step (2) is placed in a tubular furnace for transformation, the transformation temperature is 500°C, the transformation time is 1 hour, and a reducing gas (H2 / Ar atmosphere, in which the volume ratio of hydrogen and argon is 10:90) is introduced during the transformation process to obtain a transformation product.

[0076] Step (4): The transformation product obtained in step (3) is immersed in a 4M KOH solution for modification for 12 hours (the modification temperature is room temperature, for example, 10-45°C), to obtain a catalyst loaded with a porous single crystal high entropy alloy (implementation sample 1). The TEM, element distribution and HRTEM of the material are shown in FIG. Figure 1~Figure 3 .

[0077] Figure 1 This is a TEM image of the porous single crystal high entropy alloy catalyst prepared in Example 1 of the present invention. It can be seen that the multi-component alloy adheres to the surface of the carbon fiber and presents an obvious porous spatial structure.

[0078] Figure 2 This is the element distribution diagram of the porous single crystal high entropy alloy catalyst prepared in Example 1 of the present invention. It can be intuitively seen that the six elements are distributed relatively uniformly within a small size range, proving the successful preparation of the multi-element alloy.

[0079] Figure 3 HRTEM of the porous single crystal high entropy alloy catalyst prepared in Example 1 of the present invention ( Figure 3 Left) and Fourier spectrum ( Figure 3Right). After calculating the lattice spacing, the interplanar spacing in the obviously porous hollow part is 0.220nm, which is close to the Pt (111) lattice spacing, indicating that non-Pt elements are partially etched after modification and activity testing, and Pt dominates the porous structure. And the lattice pattern of the multi-component alloy particles showing a single crystal structure obtained by Fourier transform indicates the synthesis of a single crystal porous multi-component alloy.

[0080] The electrolysis of water and hydrogen evolution test of the material is as follows:

[0081] Electrochemical tests were performed on a Gamry Interface 1010E using a three-electrode system at room temperature. The prepared porous single crystal high entropy alloy catalyst was used as the working electrode, and the area in contact with the electrolyte was 1 cm. 2 , platinum sheet as counter electrode, Ag / AgCl as reference electrode. Linear sweep voltammetry curve was tested in 0.5M H2SO4 electrolyte with a scan rate of 10mV / s. During the stability test of electrochemical workstation, the prepared electrode was activated, and the three-electrode system was still used, with the current set to -500mA / cm 2 , record the change of the working electrode overpotential with time, and test the linear sweep voltammetry curve after working for 200 hours to obtain the hydrogen evolution performance data after activation.

[0082] Figure 4 It is the LSV curve of the porous single crystal high entropy alloy catalyst prepared in Example 1 of the present invention and the commercial PtC (Comparative Example 5). The figure shows that the catalyst described in the present invention reaches an overpotential of 98mV at a current of 1A and exceeds the commercial platinum carbon catalyst.

[0083] Figure 5 This is the IT curve of the porous single crystal high entropy alloy catalyst prepared in Example 1 of the present invention and commercial platinum carbon. The figure shows that the catalyst still maintains a stable voltage after 1000 hours at a current of 500 mA, while the voltage of the commercial platinum carbon catalyst increases significantly after 150 hours, and the catalytic activity gradually decreases. It can be seen that the porous single crystal high entropy alloy catalyst has excellent stability.

[0084] Example 2

[0085] Compared with Example 1, the only difference is that the current applied during the constant current electrodeposition process in step (1) is 50 mA / cm 2 , time is 10min, other operations and parameters are the same as those in Example 1. The prepared sample is named as Example 2.

[0086] Example 3

[0087] Compared with Example 1, the only difference is that the current applied during the constant current electrodeposition process in step (1) is 50 mA / cm2 , time is 30min, other operations and parameters are the same as those in Example 1. The prepared sample is named as Example 3.

[0088] Example 4

[0089] Compared with Example 1, the only difference is that the current applied during the constant current electrodeposition process in step (1) is 75 mA / cm 2 , time is 20min, other operations and parameters are the same as those in Example 1. The prepared sample is named as Example 4.

[0090] Example 5

[0091] Compared with Example 1, the only difference is that in the constant current electrodeposition process of step (1), the current applied is 100 mA / cm 2 , time is 20min, other operations and parameters are the same as those in Example 1. The prepared sample is named as Example 5.

[0092] The hydrogen evolution potentials of the materials of Examples 1 to 5 are shown in Table 1:

[0093] ; Note: 100mA / cm 2 Time-lapse potential (mV); 500mA / cm 2 Time potential (mV).

[0094] It can be seen from Examples 1 to 5 that the constant current electrodeposition described in the present invention, combined with other processes, can improve the acidic HER performance of the prepared material. In addition, the study also shows that the current of the constant current electrodeposition is 45 to 55 mA / cm 2 The constant current electrodeposition time is 20-25 minutes. This can achieve better process synergy, which helps to further improve the HER of the material under acidic conditions and the cycle stability under high current.

[0095] Example 6

[0096] Compared with Example 1, the only difference is that in the high temperature transformation process of step (3), the temperature is 500° C. and the transformation time is 0.5 h. Other operations and parameters are the same as those of Example 1. The prepared sample is named Example 6.

[0097] Example 7

[0098] Compared with Example 1, the only difference is that the temperature in the high temperature transformation process of step (3) is 500° C. and the transformation time is 2 h. Other operations and parameters are the same as those of Example 1. The prepared sample is named Example 7.

[0099] Example 8

[0100] Compared with Example 1, the only difference is that the temperature in the high temperature transformation process of step (3) is 400° C. and the transformation time is 1 h. Other operations and parameters are the same as those in Example 1. The prepared sample is named Example 8.

[0101] Example 9

[0102] Compared with Example 1, the only difference is that in the high temperature transformation process of step (3), the temperature is 600° C. and the transformation time is 1 h. Other operations and parameters are the same as those of Example 1. The prepared sample is named Example 9.

[0103] The hydrogen production performance of Examples 6 to 9 is shown in Table 2:

[0104] ; The study showed that the transformation treatment can be combined with the process to optimize the acidic HER performance of the material. In addition, the study also showed that the temperature of the transformation is 480~520℃. The holding time at the transformation temperature is 1~1.3h, which can further help to further improve the physical and chemical structure of the prepared material, improve its HER under acidic conditions and cycle stability under high current.

[0105] Example 10

[0106] Compared with Example 1, the only difference is that in the electrodeposition process of step (1), the concentration of the total metal element (the sum of metals M1, M2 and M3) in the electrodeposition solution is 0.521 mol / L, and the weight ratio of the total metal elements is 1:0.015; the ratios of other components and other operations and parameters are the same as those in Example 1. The prepared sample is named Example 10.

[0107] Embodiment 11

[0108] Compared with Example 1, the only difference is that in step (1), the molar ratio of metal M1, metal M2 and metal M3 is controlled to be 500:4:5. The total metal and other operations and parameters are the same as those in Example 1. The prepared sample is named Example 11.

[0109] Example 12

[0110] Compared with Example 1, the only difference is that in step 1, the metal M2 is a single FeCl3. The ratio of metals M1, M2, and M3 and other operations and parameters are the same as those in Example 1. The prepared sample is named Example 12.

[0111] The activity test of hydrogen production by water electrolysis of Examples 10-12 is shown in Table 3.

[0112] ; Through the control of Example 1 and Examples 10 to 12, the multi-element alloys (medium entropy alloys and high entropy alloys) described in the present invention can all show good acidic hydrogen evolution activity, but the high entropy alloy has a better effect.

[0113] Example 13

[0114] Compared with Example 1, the only difference is that the base used in the alkali solution modification process of step (4) is 4M NaOH, the modification time is 12 hours, and the other operations and parameters are the same as those of Example 1. The prepared sample is named Example 13.

[0115] Embodiment 14

[0116] Compared with Example 1, the only difference is that the base used in the alkali solution modification process of step (4) is 1M KOH, the modification time is 12 hours, and the other operations and parameters are the same as those of Example 1. The prepared sample is named Example 14.

[0117] Embodiment 15

[0118] Compared with Example 1, the only difference is that the base used in the alkali solution modification process of step (4) is 4M KOH, the modification time is 6 hours, and the other operations and parameters are the same as those of Example 1. The prepared sample is named Example 15.

[0119] The acidic hydrogen evolution results of Examples 13 to 15 are shown in Table 4:

[0120] ; In the present invention, on the basis of the constant current electrodeposition and transformation in which the metals M1 to M3 are involved, further modification treatment assisted by alkali solution is used, which is beneficial to endow the material with abundant sites, and to synergistically construct the porous-single crystal multi-component catalytic material, which is helpful to improve the HER activity of the material under acidic conditions and the stability under high current. Studies have also shown that when the alkali solution is a potassium hydroxide solution, it can further synergize and help to further improve the physical and chemical structure of the prepared material, improve its HER under acidic conditions and the cycle stability under high current.

[0121] Comparative Example 1

[0122] Compared with Example 1, the only difference is that constant voltage electrodeposition is adopted in step (1), the control voltage is -4.5 V, the time is 20 min, and the other operations and parameters are the same as those in Example 1. The prepared sample is named comparative sample 1.

[0123] Comparative Example 2

[0124] Compared with Example 1, the only difference is that the transformation process of step (3) is not performed, and step 4 modification is directly performed after step 2, and the other operations and parameters are the same as those of Example 1. The prepared sample is named comparative sample 2.

[0125] Comparative Example 3

[0126] Compared with Example 1, the only difference is that the modification process of step (4) is not performed, and the electrode material is obtained after the transformation and the electrochemical test is directly performed. The other operations and parameters are the same as those of Example 1. The obtained sample is named comparative sample 3.

[0127] Comparative Example 4

[0128] Compared with Example 1, the only difference is that the treatments in steps 1 to 4 are not performed, and the carbon felt is directly used for subsequent tests.

[0129] Comparative Example 5

[0130] Commercial platinum-carbon catalyst (Pt / C) with a mass percentage of 20%.

[0131] Comparative Example 6

[0132] Compared with Example 1, the only difference is that in the electrodeposition process of step (1), NiSO4 is used in the electrodeposition solution to replace the zinc sulfate in equal moles, and the other operations and parameters are the same as those of Example 1. The prepared sample is named Comparative Sample 6.

[0133] Comparative Example 7

[0134] Compared with Example 1, the only difference is that in the electrodeposition process of step (1), Na2MoO4 is used in the electrodeposition solution to replace the zinc sulfate in equal moles. Other operations and parameters are the same as those of Example 1. The prepared sample is named comparative sample 7.

[0135] The acidic hydrogen evolution results of each comparative example are shown in Table 5:

[0136] ; It can be seen from Example 1 and the comparative example that the present invention innovatively combines the M1~M3 type metal multi-combinations, further cooperates with the constant current electrodeposition method, the combination of current and time, and then cooperates with the subsequent transformation process and temperature and the subsequent alkali solution assisted modification, so that synergy can be achieved, and the problems of low mixing entropy of metals and metal segregation can be solved. In addition, a new catalytic material that is single crystal and porous can be constructed in situ. Studies have shown that the catalytic material with the characteristics prepared by the preparation method has excellent acidic HER catalytic activity and long cycle stability under high current.

Claims

1. A method for preparing a porous single crystal multi-element alloy catalyst, characterized in that: Obtain an electrolyte in which metal ions of M1, M2 and M3 are dissolved, place a carrier in the electrolyte for constant current electrodeposition treatment, and deposit M1-M2-M3 multi-element alloy on the carrier; wherein M1 includes at least one element of Zn, Ga, In and Sn; M2 includes at least one non-precious metal element of Fe, Co, Ni, Cu, Zn, Mn and Cr; M3 includes at least one precious metal element of Pt, Au, Ag, Pd and Ir; the total number of metal elements of M1, M2 and M3 is more than 3; the current in the constant current electrodeposition stage is 5-300 mA / cm 2 , the constant current electrodeposition time is 2min~2h; The carrier on which the M1-M2-M3 multi-element alloy is deposited is subjected to transformation treatment at a temperature of 450-850° C., and then subjected to modification treatment in an alkaline solution to obtain the porous single crystal multi-element alloy catalyst.

2. The method for preparing a porous single crystal multi-element alloy catalyst according to claim 1, characterized in that: The M1 contains zinc; The M2 comprises at least one of Fe, Co, Ni, Cu, Zn, Mn and Cr; The metal M3 includes Pt.

3. The method for preparing a porous single crystal multi-element alloy catalyst according to claim 1 or 2, characterized in that: The molar ratio of M1, M2 and M3 is 500:1-10:1-10.

4. The method for preparing a porous single crystal multi-element alloy catalyst according to claim 1, characterized in that: The carrier is at least one of carbon felt, carbon cloth, carbon paper and titanium foam; The weight ratio of the carrier to the M1-M2-M3 multi-element alloy is 1:0.001-0.

1.

5. The method for preparing a porous single crystal multi-element alloy catalyst according to claim 1, characterized in that: The current of the constant current electrodeposition is 40~100 mA / cm 2 ; The constant current electrodeposition time is 15min~1h.

6. The method for preparing a porous single crystal multi-element alloy catalyst according to claim 1, characterized in that: The transformation temperature is 450~600℃; The atmosphere during the transition phase is a reductive one; The holding time at the transition temperature is 0.5~10h.

7. The method for preparing a porous single crystal multi-element alloy catalyst according to claim 1, characterized in that: The alkali solution is an aqueous solution of an alkaline solute, wherein the alkaline solute includes at least one of an alkali metal hydroxide and a carbonate; In the alkali solution, the concentration of the alkaline solute is 0.1~5M; The time for modification of the product after transformation treatment in alkaline solution is 2~24h.

8. A porous single crystal multi-element alloy catalyst prepared by the preparation method according to any one of claims 1 to 7.

9. An application of a porous single crystal multi-element alloy catalyst prepared by the preparation method according to any one of claims 1 to 7, characterized in that: It is used as a HER catalytic active component to catalyze the hydrogen evolution reaction in acidic solutions.

10. A water electrolysis device, characterized in that: A porous single crystal multi-element alloy catalyst prepared by the preparation method according to any one of claims 1 to 7, or prepared by the porous single crystal multi-element alloy catalyst.

Citation Information

Patent Citations

  • FeCoNiWCuOOH-coated Cu electrocatalyst as well as preparation method and application thereof

    CN118166391A

  • Difunctional high-entropy nano-alloy electrocatalyst and preparation method thereof

    CN116288477A

  • Multi-element metal hydroxide self-supporting integrated activation electrode and preparation and application thereof

    CN119121282A

  • Electrocatalyst for water electrolysis and preparing method of the same

    US20220259748A1

Cited By

  • Multi-grain-boundary ZnFeCoNiMnCu-coated Cu water electrolysis catalyst as well as preparation method and application thereof

    CN120666376A